Magnetic ternary chalcogenide two-dimensional nanosheet material as well as preparation method and application thereof

By developing magnetic ternary oxygen group two-dimensional nanosheet-like materials, the problem of specific imaging and insufficient versatility in early tumor detection and treatment is solved, and efficient tumor targeted imaging and treatment is achieved, with excellent photothermal Conversion performance and multimodal development performance.

CN119236068APending Publication Date: 2025-01-03THE AFFILIATED HOSPITAL OF SOUTHWEST MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411152946.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing technology lacks specific imaging methods in early tumor detection. Traditional MRI, CT and PET-CT have insufficient sensitivity and resolution. Traditional treatment methods have toxic side effects on normal tissues. The photothermal conversion efficiency of photothermal therapy is low and Insufficient versatility.

Method used

Develop a magnetic ternary oxygen group two-dimensional nanosheet-like material with a chemical structure of ABC2@ targeted ligand, prepared by specific synthetic methods, for tumor CT and MRI imaging and treatment, the material has high photothermal conversion efficiency and Multimodal development performance.

Benefits of technology

It has achieved efficient tumor-targeted imaging and treatment, with good photothermal conversion performance and MRI/CT multimodal development performance, and can undergo chemotherapy and photothermal therapy simultaneously to reduce damage to normal tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236068A_ABST
    Figure CN119236068A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic ternary chalcogenide two-dimensional nanosheet material as well as a preparation method and application thereof, and belongs to the technical field of biological medicines. The chemical structural general formula of the material is ABC2 at a targeting ligand, in which A is Cu or Ag, B is a ferromagnetic element, and C is S, Se or Te. The magnetic ternary two-dimensional nanosheet material is simple to operate and easy to popularize, and the magnetic ternary two-dimensional nanosheet material can be used for achieving CT enhanced imaging of related diseases, MRI enhanced imaging, related disease treatment and other biomedical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedicine, and specifically relates to a magnetic ternary oxygen family two-dimensional nanosheet material and a preparation method and use thereof. Background Art

[0002] At present, the main problem facing the accurate early detection of tumors in clinical practice is the lack of specific imaging methods. A variety of imaging methods have been used for preoperative evaluation of tumors, including ultrasound, computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET-CT) and other examination techniques. Ultrasound is the preferred examination method for diagnosing tumors. It is radiation-free, non-invasive and low-cost, but it is greatly affected by the operator's clinical experience, proficiency, patient obesity and cooperation, gastrointestinal bloating and costal arch coverage, thereby reducing the detection rate of tumors, and it is unable to diagnose early lesions that have not yet caused morphological and echo changes.

[0003] CT is an important means of diagnosing tumors, but it is not the best imaging method for tumor lesion characteristics, and it has ionizing radiation. Although PET-CT can visualize primary lesions and metastatic lesions, it is expensive, its fusion image lesion spatial resolution is not high, and there are disadvantages such as radioactive radiation and low specificity for lesion localization. MRI is currently the best method for diagnosing CCA. It has high resolution for soft tissues and no ionizing radiation. It is the preferred clinical imaging method for evaluating and diagnosing tumors. However, conventional MRI technology has low targeting and detection sensitivity, and poor display of early lesions and smaller lesions, which cannot fully meet clinical needs.

[0004] Tumors seriously threaten human life and health. How to achieve early and accurate diagnosis and treatment of tumors is an important strategy to reduce their high mortality rate. At present, single imaging technology is mainly used in clinical practice to detect tumors. Imaging technologies have their own advantages and disadvantages in terms of sensitivity and resolution. Therefore, the use of multimodal imaging with complementary advantages is of great help in the early and accurate diagnosis of tumor lesions. Therefore, the development of multimodal contrast agents with strong tumor targeting and high sensitivity for early diagnosis and targeted treatment of tumors will have important clinical significance.

[0005] Traditional methods of tumor treatment mainly include surgery, chemotherapy and radiotherapy. In many cases, surgical treatment cannot completely eliminate all cancer cells in the human body. Chemotherapy and radiotherapy not only kill cancer cells but also have serious toxic side effects on normal tissues. Compared with traditional treatment methods, the newly developed photothermal therapy, especially photothermal therapy based on near-infrared fluorescence (NIRF), has attracted much attention. This method can selectively kill cancer cells through less toxic photothermal converters without causing too much damage to normal tissues. For example, the spherical CuFeSe2 nanoparticles reported in the early stage have unique advantages and potential application value in nanobiomedical fields such as in vivo multimodal imaging, tumor photothermal therapy and anti-tumor drug delivery, but there are problems of low photothermal conversion efficiency and insufficient versatility. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a magnetic ternary oxygen-based two-dimensional nanosheet material and a preparation method and use thereof. The synthesis method provided by the present invention has high yield, simple operation and easy promotion. The prepared magnetic ternary two-dimensional nanosheet material can be used for biomedical applications such as tumor CT imaging, MRI imaging and treatment.

[0007] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0008] A magnetic ternary oxygen-based two-dimensional nanosheet material has a general chemical structure of: ABC2@targeting ligand, wherein A is Cu or Ag, B is a ferromagnetic element, and C is S, Se or Te.

[0009] Furthermore, in the general chemical structure formula, A is Cu or Ag, B is a ferromagnetic element, and C is Se or S.

[0010] Furthermore, in the general chemical structure formula, A is Cu, B is Mn or Fe, and C is Se.

[0011] Furthermore, the targeting ligand is hyaluronic acid, lactobionic acid, folic acid, biotin, estradiol, plerixafor, indomethacin, gemcitabine and its derivatives with a molecular weight of 3000-10000000.

[0012] The method for preparing the above-mentioned magnetic ternary oxygen-based two-dimensional nanosheet material comprises the following steps:

[0013] (1) dissolving substance B, adding the targeting ligand solution, and stirring to mix;

[0014] (2) Mix and dissolve substance C and a reducing agent, then add them to the solution obtained in step (2), stir for reaction, and then add substance A solution to continue the reaction, thereby obtaining the magnetic ternary oxygen-based two-dimensional nanosheet material.

[0015] Furthermore, the mass concentration of substance B after dissolution is 10 to 900 mg / L, which is chloride, nitrate, sulfate, acetate or hydrate containing B; the mass concentration of the targeting ligand after dissolution is 100 to 1000 mg / L.

[0016] Furthermore, the mass concentration of substance C after dissolution is 10 to 900 mg / L, and it is a single substance powder, or a chloride, nitrate, sulfate, acetate or hydrate containing C.

[0017] Furthermore, the mass concentration of the reducing agent after dissolution is 10 to 900 mg / L, and the reducing agent is at least one of sodium borohydride, potassium borohydride, and sodium triacetoxyborohydride.

[0018] Furthermore, the mass concentration of substance A after dissolution is 10 to 900 mg / L, and it is a chloride, nitrate, sulfate, acetate or hydrate containing A.

[0019] Furthermore, the mass ratio of substance A, substance B and substance C is 5-10:5-10:20-30.

[0020] Furthermore, the mass ratio of substance A, substance B and substance C is 64:56:158.

[0021] Furthermore, the stirring reaction temperature in step (1) and step (2) is 20 to 100° C., and the stirring speed is 50 to 2500 r / min.

[0022] A tumor targeted therapeutic drug comprises the above-mentioned magnetic ternary oxygen family two-dimensional nanosheet material.

[0023] The use of the above-mentioned magnetic ternary oxygen-based two-dimensional nanosheet material in the preparation of tumor-specific CT or MRI contrast agents.

[0024] An anti-tumor targeted drug composition, comprising the above-mentioned magnetic ternary oxygen-based two-dimensional nanomaterial, and one or more pharmaceutically acceptable carriers or excipients, can be used in biomedical fields such as computed tomography imaging, magnetic resonance imaging, tumor therapy and photothermal therapy.

[0025] Beneficial effects of the present invention:

[0026] The present invention prepares a magnetic ternary oxygen family two-dimensional nanosheet material. The ultra-high surface area and volume ratio of the two-dimensional nanosheet material has significant advantages for drug delivery systems that require large-scale surface interactions. The ultra-thin thickness enables it to quickly respond to external light stimulation. Compared with ternary nanocrystals with a wider band gap, the two-dimensional nanosheet has a smaller band gap. This property enables a higher photothermal conversion efficiency to be obtained under infrared light irradiation, making it have good photothermal performance and better photothermal conversion performance. In addition, due to the magnetic Fe 3+ Due to the presence of and small nanometer size effect, Cu-Fe-Se nanomaterials also show superparamagnetism; the relatively high effective atomic number and X-ray attenuation coefficient give them good X-ray imaging performance.

[0027] Compared with the prior art, the tumor-targeted Cu-Fe-Se two-dimensional nanomagnetic ternary nanosheet material prepared by the present invention has better photothermal conversion performance, more excellent MRI and CT multimodal development performance, and can simultaneously achieve photothermal therapy and chemotherapy synergistic multi-component synergistic treatment of malignant tumors, and is expected to be used in the integrated clinical diagnosis and treatment of tumors.

[0028] The magnetic ternary oxygen-based two-dimensional nanomaterial prepared by the present invention can be used as a tumor-specific developer and anti-tumor drug, and can also be used with one or more pharmaceutically acceptable carriers or excipients as an imaging enhancement contrast agent and an anti-tumor drug composition. The preparation method is effective and reasonable, has a high yield, is simple to operate, and is easy to promote. It can be prepared according to existing conventional medical technology and has good biological safety. This type of magnetic ternary two-dimensional nanosheet material can be used in biomedical applications such as CT imaging, MRI imaging, tumor treatment, and photothermal therapy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a transmission electron microscopy image of the hyaluronic acid-modified ternary magnetic two-dimensional nanosheet CuFeSe2@hyaluronic acid prepared in Example 1 of the present invention;

[0030] Figure 2 This is the infrared spectrum of the ternary magnetic two-dimensional nanosheet CuFeSe2@hyaluronic acid modified with hyaluronic acid prepared in Example 1 of the present invention;

[0031] Figure 3 H&E pathological staining images of the main organs of normal mice after administration of the hyaluronic acid-modified ternary magnetic two-dimensional nanosheets CuFeSe2@hyaluronic acid (0.5mmol Fe / kg) prepared in Example 1 of the present invention for 1 day and 14 days;

[0032] Figure 4The temperature rise curves of the ternary magnetic two-dimensional nanosheets CuFeSe2@hyaluronic acid modified with hyaluronic acid prepared in Example 1 of the present invention at different concentrations under 808nm laser irradiation;

[0033] Figure 5 The T2MRI images of the tumor at different time points after intravenous administration of the hyaluronic acid-modified ternary magnetic two-dimensional nanosheets CuFeSe2@hyaluronic acid (0.5 mmol Fe / kg) prepared in Example 1 of the present invention to the thigh root of 4T1 tumor-bearing mice;

[0034] Figure 6 This is a transmission electron microscope image of the ternary magnetic two-dimensional nanosheet CuFeSe2@folic acid-biotin modified with folic acid and biotin prepared in Example 2 of the present invention;

[0035] Figure 7 This is an infrared spectrum of the ternary magnetic two-dimensional nanosheet CuFeSe2@folic acid-biotin modified with folic acid and biotin prepared in Example 2 of the present invention;

[0036] Figure 8 This is an X-ray diffraction pattern of the ternary magnetic two-dimensional nanosheet CuFeSe2@folic acid-biotin modified with folic acid and biotin prepared in Example 2 of the present invention;

[0037] Fig. 9 The blood biochemical indexes of normal mice administered with the ternary magnetic two-dimensional nanosheets CuFeSe2@folic acid-biotin (0.5mmol Fe / kg) co-modified with folic acid and biotin prepared in Example 2 of the present invention for 1 day and 14 days;

[0038] Fig.10 The transmission electron microscope image and elemental energy spectrum of the ternary magnetic two-dimensional nanosheet CuFeSe2@lactobionic acid modified by lactobionic acid prepared in Example 3 of the present invention;

[0039] Fig.11 This is an infrared spectrum of the lactobionic acid-modified ternary magnetic two-dimensional nanosheet CuFeSe2@lactobionic acid prepared in Example 3 of the present invention;

[0040] Fig.12 This is an X-ray diffraction pattern of the lactobionic acid-modified ternary magnetic two-dimensional nanosheet CuFeSe2@lactobionic acid prepared in Example 3 of the present invention;

[0041] Fig.13 The transmission electron microscope image and elemental energy spectrum of the ternary magnetic two-dimensional nanosheet CuFeSe2@AMD3100-Gem co-modified with plerixafor and gemcitabine prepared in Example 4 of the present invention;

[0042] Fig.14 The in vitro CT imaging images, nuclear magnetic resonance images and relaxation rate curves of different concentrations of the ternary magnetic two-dimensional nanosheet CuFeSe2@AMD3100-Gem co-modified with plerixafor and gemcitabine prepared in Example 4 of the present invention are shown;

[0043] Fig.15 The CT and T2MRI images of the tumor at different time points after intravenous administration of the ternary magnetic two-dimensional nanosheets CuFeSe2@AMD3100-Gem (0.5mmol Fe / kg) co-modified with plerixafor and gemcitabine prepared in Example 4 of the present invention to the thigh root of 4T1 tumor-bearing mice;

[0044] Fig.16 This is a diagram showing the therapeutic effect of the ternary magnetic two-dimensional nanosheets CuFeSe2@AMD3100-Gem (0.5 mmol Fe / kg) co-modified with plerixafor and gemcitabine prepared in Example 4 of the present invention after intravenous administration to 4T1 tumor-bearing mice and 808 nm laser irradiation. DETAILED DESCRIPTION

[0045] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0046] Example 1

[0047] A magnetic ternary oxygen-based two-dimensional nanosheet material CuFeSe2@hyaluronic acid, the preparation method of which is as follows:

[0048] (1) In a nitrogen atmosphere, add 100 mg of sodium borohydride and 80 mg of selenium powder to 200 mL of deionized water, stir at 25°C and 1500 r / min for 2 hours and set aside;

[0049] (2) In another reaction bottle, 400 mg of hyaluronic acid and 140 mg of ferrous sulfate heptahydrate were dissolved in 100 mL of water, stirred for 30 minutes, and then the selenium-containing solution prepared in step (1) was added. After stirring for 30 minutes, 90 mg of cuprous chloride was added and reacted for 2 hours. After the reaction was complete, the mixture was centrifuged and washed, and vacuum dried to obtain a black powder. The obtained hyaluronic acid-modified ternary magnetic two-dimensional nanosheet CuFeSe2@hyaluronic acid had a transmission electron microscope image and an infrared spectrum as shown in FIG. Figure 1 and Figure 2 .

[0050] like Figure 1As shown, the CuFeSe2@hyaluronic acid sample nanocrystal prepared in this example has an irregular lamellar structure. In addition, it exhibits characteristic peaks of CuFeSe2 and hyaluronic acid, indicating that hyaluronic acid has a coordination effect with the surface metal atoms of the CuFeSe2 nanocrystal. Figure 2 )

[0051] Example 2

[0052] A magnetic ternary oxygen-based two-dimensional nanosheet material CuFeSe2@folic acid-biotin, the preparation method of which is as follows:

[0053] (1) In a nitrogen atmosphere, add 100 mg of sodium borohydride and 80 mg of selenium powder to 200 mL of deionized water, stir at 25°C and 1500 r / min for 2 hours and set aside;

[0054] (2) In another reaction bottle, folic acid polyethylene glycol lipoic acid (molecular weight 2000) and 200 mg biotin polyethylene glycol lipoic acid (molecular weight 2000) and 140 mg ferric sulfate heptahydrate were dissolved in 100 mL water, stirred for 30 minutes, and then the selenium-containing solution prepared in step (1) was added, and stirring was continued for 30 minutes, and then 90 mg cuprous chloride aqueous solution was added to react for 2 hours. After the reaction was complete, the powder was washed by centrifugation and vacuum dried to obtain a black powder. The obtained folic acid and biotin co-modified ternary magnetic two-dimensional nanosheet CuFeSe2@folic acid-biotin had a transmission electron microscope image, infrared spectrum and X-ray diffraction pattern as shown in FIG. Figures 6 to 8 .

[0055] like Figure 6 As shown, the CuFeSe2@hyaluronic acid sample nanocrystal prepared in this example has an irregular lamellar structure. At the same time, characteristic peaks of CuFeSe2, folic acid polyethylene glycol lipoic acid and biotin polyethylene glycol lipoic acid are shown, indicating that the targeting ligand (folic acid polyethylene glycol lipoic acid and biotin polyethylene glycol lipoic acid) has a coordination effect with the surface metal atoms of the CuFeSe2 nanocrystal. ( Figure 7 )

[0056] Then the prepared material sample powder was placed in an X-ray powder diffractometer for detection. The detection conditions were a 2θ angle range of 10-90° and a scanning rate of 6° / min to analyze the crystal structure of the sample. The XRD results were consistent with the standard card JCPDS NO.81-1959. ( Figure 8 )

[0057] Example 3

[0058] A magnetic ternary oxygen-based two-dimensional nanosheet material CuFeSe2@lactose acid, the preparation method of which is as follows:

[0059] (1) In a nitrogen atmosphere, add 100 mg of sodium borohydride and 80 mg of selenium powder to 200 mL of deionized water, stir at 25°C and 1500 r / min for 2 hours and set aside;

[0060] (2) In another reaction bottle, 300 mg of lactobionic acid and 140 mg of ferric sulfate heptahydrate were dissolved in 100 mL of water, stirred for 30 minutes, and then the selenium-containing solution prepared in step (1) was added, and then stirred for 30 minutes, and then 90 mg of cuprous chloride was added to the aqueous solution for reaction for 2 hours. After the reaction was complete, the powder was centrifuged and washed, and vacuum dried to obtain a black powder. The obtained lactobionic acid-modified ternary magnetic two-dimensional nanosheet CuFeSe2@lactobionic acid had a transmission electron microscope-element spectrum, infrared spectrum, and X-ray diffraction pattern as shown in FIG. Figures 10-12 .

[0061] like Fig.10 As shown, the CuFeSe2@hyaluronic acid sample nanocrystal prepared in this example has an irregular lamellar structure, and the spectrum test shows that it contains three elements: Cu, Fe, and Se. The surface functional groups of the prepared CuFeSe2@lactobionic acid were determined by infrared spectrometer, which showed characteristic peaks of CuFeSe2 and lactobionic acid, indicating that lactobionic acid has coordination effect with the surface metal atoms of CuFeSe2 nanocrystals. ( Fig.11 )

[0062] Then the prepared material sample powder was placed in an X-ray powder diffractometer for detection. The detection conditions were a 2θ angle range of 10-90° and a scanning rate of 6° / min to analyze the crystal structure of the sample. The XRD results were consistent with the standard card JCPDS NO.81-1959. ( Fig.12 )

[0063] Example 4

[0064] A magnetic ternary oxygen-based two-dimensional nanosheet material CuFeSe2@AMD3100-Gem, the preparation method of which is as follows:

[0065] (1) In a nitrogen atmosphere, add 100 mg of sodium borohydride and 80 mg of selenium powder to 200 mL of deionized water, stir at 25°C and 1500 r / min for 2 hours and set aside;

[0066] (2) In another reaction bottle, 200 mg of plerixafor polyethylene glycol lipoic acid (molecular weight 2000) and 200 mg of gemcitabine polyethylene glycol lipoic acid (molecular weight 2000) and 140 mg of ferric sulfate heptahydrate were dissolved in 100 mL of water, stirred for 30 minutes, and then the selenium-containing solution prepared in step (1) was added, and then stirred for 30 minutes and then 90 mg of cuprous chloride aqueous solution was added to react for 2 hours. After the reaction is complete, the mixture is centrifuged and washed, and vacuum dried to obtain a black powder. The obtained ternary magnetic two-dimensional nanosheet CuFeSe2@AMD3100-Gem co-modified with plerixafor and gemcitabine has a transmission electron microscope image and elemental energy spectrum as shown in FIG. Fig.13 .

[0067] like Fig.13 As shown, the CuFeSe2@hyaluronic acid sample nanocrystals prepared in this example are irregular lamellar structures, and the energy spectrum test shows that the three elements Cu, Fe, and Se are evenly distributed in the material.

[0068] Experimental example

[0069] 1. Performance measurement of CuFeSe2@hyaluronic acid prepared in Example 1

[0070] (1) Photothermal conversion performance testing

[0071] Prepare a series of CuFeSe2@hyaluronic acid sample solutions with a concentration gradient, such as 0 μg / mL, 50 μg / mL, 100 μg / mL, 200 μg / mL, and 400 μg / mL. Take 1 mL of each solution into a 1 cm×1 cm×2 cm quartz cuvette and heat at 1, 1.5, and 2 W / cm 2 The power density of 808nm laser was irradiated for 5 minutes and then the laser was turned off. During this period, the real-time temperature change data of the solution in the cuvette was monitored by an infrared thermal imager. The results are shown in Figure 4 .

[0072] like Figure 4 As shown in the figure, the temperature of CuFeSe2@hyaluronic acid aqueous solution under 808nm laser irradiation increases significantly with the increase of concentration. The above data prove that CuFeSe2@hyaluronic acid does have good photothermal conversion performance. For solutions of the same concentration, we found that the temperature increase effect of flake CuFeSe2 nanomaterials is higher than that of spherical CuFeSe2 nanomaterials.

[0073] (2) Impact on tissues and organs

[0074] Eighteen healthy female BABL / C mice aged 6-8 weeks were divided into two groups (experimental group n=15, blank group n=3). The mice in the experimental group were injected with 0.1 ml, 5 mg / mL CuFeSe2@hyaluronic acid sample solution (25 mg / kg, solvent is 5% glucose injection) through the tail vein, and the blank group was injected with 0.1 ml 5% glucose injection. The activity and eating conditions of the mice were observed. Three mice in the experimental group were killed on the 1st, 3rd, 5th, 10th and 15th day after injection, respectively, and the mice in the blank group were killed on the 15th day. Important tissues and organs (heart, liver, spleen, lung, kidney, left thigh muscle) were taken, fixed with 4% formalin solution, embedded in paraffin, sliced, and stained with H&E. The results are shown in Figure 3 .

[0075] like Figure 3 As shown in the figure, H&E analysis showed that the microscopic structures of important organs such as myocardial fibers, liver lobules, germinal centers, bronchioles, alveolar sacs, glomeruli, and renal tubules were neatly arranged without obvious histopathological damage. Compared with the control group, there was basically no tissue necrosis, tissue disorder, and inflammatory reaction.

[0076] (3) T2MRI imaging performance

[0077] Mouse breast cancer 4T1 cells in the logarithmic growth phase were digested, centrifuged, and counted before being prepared into 1×10 6 The concentration of cells / mL (solvent is PBS) was 0.2 ml of cell suspension was injected subcutaneously at the ventral side of the right thigh root. The mental and activity status of the mice was observed every day, and the tumor volume was measured. When the tumor volume reached 100 mm 3 The modeling was successful. Five mice with successfully modeled 4T1 tumors were divided into an experimental group (n=3) and a control group (n=2). The mice were anesthetized by intraperitoneal injection of 5% chloral hydrate. The mice were fixed on a fixed board and placed in a wrist joint coil. The mice were scanned by T2WI sequence using 3.0T Prisma MR. After the first scan, the mice in the experimental group were injected with 0.1mL, 5mg / mL CuFeSe2@hyaluronic acid sample (prepared with 5% glucose injection) through the tail vein, and the mice in the control group were injected with 0.1ml, 5% glucose injection through the tail vein. The second scan was performed immediately after the injection, and then repeated sequence scans were taken on the mice at different time points after the injection. The T2WI image of the largest layer of the tumor was selected on the MR post-processing workstation. The T2WI sequence scanning conditions were as follows: TR=5290ms, TE=70ms, layer thickness=2mm, matrix 256×256, FOV=120mm. The scanning conditions of the T2*map sequence are as follows: TR = 293.0 ms, TE = 2.98 ms, slice thickness = 2 mm, matrix 256 × 256, FOV = 120 mm, flip angle 60°, and the results are shown in Figure 5.

[0078] like Figure 5 As shown in the figure, after the injection of CuFeSe2@hyaluronic acid sample, the tumor began to show uneven enhancement, and the signal on the T2WI sequence gradually decreased. The tumor enhancement was most obvious at 7h, and the T2 signal was the lowest. The above experimental results show that the CuFeSe2@hyaluronic acid sample has excellent tumor targeting and can achieve MRI targeted molecular imaging of 4T1 tumors in vivo.

[0079] 2. Effects of CuFeSe2@folic acid-biotin prepared in Example 1 on blood biochemical indicators after administration

[0080] The mice were randomly divided into an experimental group and a control group. The mice in the experimental group were injected with CuFeSe2@folic acid-biotin samples (0.1 mL, 5 mg / mL) through the tail vein for 1 day and 14 days; the mice in the control group (n=4) were injected with normal saline through the tail vein. After the mice were anesthetized, the hair around the eye sockets of the mice in the experimental and control groups needed to be trimmed clean to prevent debris and hair from entering the blood, causing contamination and hemolysis. The eyeballs of the mice were then removed with tweezers to obtain fresh blood. The fresh blood was quickly placed in a centrifuge and centrifuged at 950 rpm for 5 minutes and then allowed to stand for 10 minutes. At this time, stratified blood appeared, and the supernatant was aspirated with a pipette. This supernatant was mouse serum. The mouse serum was stored in bags at low temperature and sent to the laboratory of the Affiliated Hospital of Southwest Medical University in time to test typical biochemical markers, namely liver and kidney function indicators. The results are shown in the table below. Fig. 9 .

[0081] like Fig. 9 As shown, compared with the control group, there were no significant differences in liver function indicators such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and typical biomarkers of renal function such as uric acid (UA) and creatinine (CREA) on days 1 and 14.

[0082] 3. Performance measurement of CuFeSe2@AMD3100-Gem prepared in Example 4

[0083] (1) CT imaging, MRI and relaxation rate detection

[0084] CuFeSe2@AMD3100-Gem samples were prepared with distilled water solutions containing different Fe concentrations (0μmol / L, 0.575μmol / L, 11.5μmol / L, 23μmol / L, 46μmol / L). After ultrasonic dispersion, T2WI, T2map, T1WI, and T1map were scanned using Prisma 3.0T MR. T2 and T1 values ​​were measured using Siemens post-processing, and the relaxation rate was calculated. MR scanning conditions are as follows: T2WI: TR = 2000ms, TE = 96ms, FOV = 180mm, and slice thickness = 1.4mm. T2map: TR = 2000ms, TE = 12.9ms, FOV = 250mm, and slice thickness = 1.0mm. T1WI: TR = 600ms, TE = 7.5ms, FOV = 180mm, and slice thickness = 1.4mm. T1map: TR=5.28ms, TE=2.47ms, FOV=250mm, slice thickness=1.0mm.

[0085] Solutions with the same I or Cu concentration (0, 0.75 μmol / L, 1.5 μmol / L, 3 μmol / L, 6 μmol / L) were prepared with iohexol and CuFeSe2@AMD3100-Gem sample powders, and ultrasonic dispersion was uniform. Conventional CT and spectral CT scanning were performed using IQon CT. The CT value and effective atomic number were measured using a Philips post-processing workstation. The CT scanning conditions were as follows: 120 KV, 100 mAs, 40 keV, FOV = 150 mm, 512 × 512 matrix, slice thickness = 0.8 mm, measurement window width 180, window position 70, measurement area 10.55 mm 2 The results are shown in Fig.14 .

[0086] like Fig.14 As shown in Figure 2, the transverse relaxation rate and longitudinal relaxation rate of the CuFeSe2@AMD3100-Gem sample at a magnetic field strength of 3.0 T are 6.68 mM -1 S -1 and 0.43mM -1 S -1 , indicating that it has the potential to be used as a T2WI contrast enhancement agent. In addition, the effective atomic coefficient of the spherical CuFeSe2 nanomaterial is 49.85, and the attenuation coefficient under 60keV X-ray is 1.94cm 2 / g. Compared with iohexol, a commonly used CT contrast agent in clinical practice, CuFeSe2@AMD3100-Gem has better X-ray attenuation performance, and there is an obvious linear dependence between concentration and signal intensity. It is superior to iohexol and spherical CuFeSe2 nanomaterials, indicating that it has application potential in CT imaging.

[0087] (2) CT and T2MRI imaging of tumors at different time points after intravenous administration in mice

[0088] Mouse breast cancer 4T1 cells in the logarithmic growth phase were digested, centrifuged, and counted before being prepared into 1×10 6 The concentration of cells / mL (solvent is PBS) was 0.2 ml of cell suspension was injected subcutaneously at the ventral side of the right thigh root. The mental and activity status of the mice was observed every day, and the tumor volume was measured. When the tumor volume reached 100 mm 3 The model was successfully established. The five mice with successfully established 4T1 tumors were divided into an experimental group (n=3) and a control group (n=2). The mice were anesthetized by intraperitoneal injection of 5% chloral hydrate. The mice were fixed on a fixed board and placed in a wrist joint coil. The mice were scanned by T2WI sequence using 3.0T Prisma MR. After the first scan, the mice in the experimental group were injected with 0.1mL, 5mg / mL CuFeSe2@AMD3100-Gem sample (prepared with 5% glucose injection) through the tail vein, and the mice in the control group were injected with 0.1ml, 5% glucose injection through the tail vein. The second scan was performed immediately after the injection, and then repeated sequence scans were taken on the mice at different time points after the injection. The T2WI image of the largest layer of the tumor was selected on the MR post-processing workstation, and the results are shown in the figure. Fig.15 The scanning conditions of T2WI sequence were as follows: TR = 5290 ms, TE = 70 ms, slice thickness = 2 mm, matrix 256 × 256, FOV = 120 mm. The scanning conditions of T2*map sequence were as follows: TR = 293.0 ms, TE = 2.98 ms, slice thickness = 2 mm, matrix 256 × 256, FOV = 120 mm, flip angle 60°.

[0089] The mice with successfully modeled 4T1 tumors were anesthetized with 5% chloral hydrate intraperitoneally and fixed on a fixed board. IQon CT was used to perform conventional CT and spectral CT scans on the mice before injection. After the scan, 0.1 ml, 5 mg / mL CuFeSe2@AMD3100-Gem sample (prepared with 5% glucose injection) was injected into the tumor without changing the mouse's position, and a CT scan was performed immediately after injection. After the scan, the Philips CT post-processing workstation was used to select the largest slice image of the tumor, outline the largest area of ​​interest, and measure the average CT value and average effective atomic number in the tumor. The CT scanning conditions are as follows:

[0090] 120KV, 60mAs, 50keV, FOV=150mm, matrix 512×512, slice thickness=0.8mm, window width=200HU, window position=100HU. CT imaging of the sample before and after intratumoral injection of CuFeSe2@AMD3100-Gem is shown in Fig.15 .

[0091] like Fig.15 As shown, by comparing the conventional CT scan images before and after injection, it was found that the density of the tumor site increased after injection, and the CT value was higher than that before injection. Comparing the energy spectrum CT before and after injection, the image color after injection became brighter, and the effective atomic number value was slightly higher than that before injection. Therefore, the present invention believes that the CuFeSe2@AMD3100-Gem sample can increase the CT value in the tumor tissue.

[0092] MRI results showed that after injection of the targeted CuFeSe2@AMD3100-Gem sample, the tumor began to show uneven enhancement, and the signal gradually decreased on the T2WI sequence. The tumor enhancement was most obvious at 6 hours, and the T2 signal was the lowest. The above experimental results show that CuFeSe2@AMD3100-Gem has excellent tumor targeting and can achieve CT / MRI dual-modality targeted molecular imaging of 4T1 tumors in vivo.

[0093] (3) Detection of therapeutic efficacy of intravenous administration on tumors in mice

[0094] The tumor-bearing 4T1 model mice were divided into 4 groups, including the control group, the laser irradiation group, the drug administration group, and the drug administration + laser irradiation group. The treatment methods were as follows: the control group did not receive any treatment, the control group was injected with 200 μL PBS, the drug administration group was injected with 100 μL CuFeSe2@AMD3100-Gem sample solution (5 mg / mL), and the laser irradiation group was injected with 200 μL PBS and then irradiated with 808 nm laser (power density of 0.75 W / cm 2 ) irradiated the tumor site for 5 min, and the drug administration + laser irradiation group was injected with 200 μL CuFeSe2@AMD3100-Gem solution (5 mg / mL) and then irradiated with 808 nm laser (power density of 0.75 W / cm 2 ) irradiated the tumor site for 5 minutes. Before treatment, 1% pentobarbital (150 μL) was used to anesthetize the rats by intraperitoneal injection. During the hyperthermia treatment, the temperature changes of the tumor site of the rats were recorded in real time using an infrared thermal imager. The results are shown in Fig.16 .

[0095] like Fig.16 As shown, 15 days after treatment, the tumors in the treated group mice had complete new skin, and there was no recurrence in the following ten days, indicating that the tumor was completely cured; in the other three groups, the tumors continued to grow, indicating that the treatment effect was not achieved.

[0096] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A magnetic ternary oxygen-based two-dimensional nanosheet material, characterized in that: Its general chemical structure formula is: ABC2@targeting ligand, wherein A is Cu or Ag, B is a ferromagnetic element, and C is S, Se or Te.

2. The magnetic ternary oxygen-based two-dimensional nanosheet material according to claim 1, characterized in that: In the general chemical structure formula, A is Cu or Ag, B is a ferromagnetic element, and C is Se or S.

3. The magnetic ternary oxygen-based two-dimensional nanosheet material according to claim 1, characterized in that: The targeting ligand is hyaluronic acid, lactobionic acid, folic acid, biotin, estradiol, plerixafor, indomethacin, gemcitabine and derivatives thereof with a molecular weight of 3000-10000000.

4. A method for preparing the magnetic ternary oxygen-based two-dimensional nanosheet material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving substance B, adding the targeting ligand solution, and stirring to mix; (2) Mix and dissolve substance C and a reducing agent, then add them to the solution obtained in step (2), stir for reaction, and then add substance A solution to continue the reaction, thereby obtaining the magnetic ternary oxygen-based two-dimensional nanosheet material.

5. The preparation method according to claim 4, characterized in that: The mass concentration of substance B after dissolution is 10 to 900 mg / L, which is a chloride, nitrate, sulfate, acetate or hydrate containing B; The mass concentration of the targeting ligand after dissolution is 100-1000 mg / L.

6. The preparation method according to claim 4, characterized in that: The mass concentration of substance C after dissolution is 10 to 900 mg / L, and it is a single substance powder, or a chloride, nitrate, sulfate, acetate or hydrate containing C; The mass concentration of the reducing agent after dissolution is 10-900 mg / L, and the reducing agent is at least one of sodium borohydride, potassium borohydride, and sodium triacetoxyborohydride.

7. The preparation method according to claim 4, characterized in that: The mass concentration of substance A after dissolution is 10 to 900 mg / L, and the substance A is a chloride, nitrate, sulfate, acetate or a hydrate thereof.

8. The preparation method according to claim 4, characterized in that: The stirring reaction temperature in step (1) and step (2) is 0 to 100°C.

9. A tumor targeted therapeutic drug, characterized in that: The invention comprises the magnetic ternary oxygen-based two-dimensional nanosheet material as described in any one of claims 1 to 3.

10. Use of the magnetic ternary oxygen-based two-dimensional nanosheet material according to any one of claims 1 to 3 in the preparation of tumor-specific CT and / or MRI contrast agents.